Implementation Of Learning Based On Creative Thinking Skills Using Augmented Reality To Improve Academic Achievement Of Students In Computer Assembly Courses - Reni Rahmadani; Tansa Trisna Astono Putri; Muhammad Dominique Mendoza; Olnes Hutajulu; Elsa Sabrina (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2026)
This study aims to evaluate the effectiveness of implementing Creative Thinking Skills (CTS)-based learning using Augmented Reality (AR) media to improve students’ academic achievement in the Computer Assembly course. The research employed a quantitative approach with a quasi-experimental method and a one-group pretest–posttest design. The subjects consisted of 30 undergraduate students of the Information and Computer Technology Education Study Program at Universitas Negeri Medan. The instruments used included a learning outcomes test, a CTS assessment rubric, and a student satisfaction questionnaire toward AR media. The learning outcomes were analyzed using the Normalized Gain (N-Gain) test, while the CTS scores were examined using a paired t-test, and the satisfaction data were analyzed descriptively. The findings showed that the use of AR significantly improved students’ learning outcomes with an average N-Gain value of 0.72 (high category). The students’ CTS scores also increased across all indicators—fluency, flexibility, originality, and elaboration—achieving an overall category of “highly creative.” Furthermore, the average satisfaction score of 4.26 (out of 5) indicated that students were very satisfied with AR-based learning. These results demonstrate that integrating AR media with CTS-based learning effectively enhances both academic performance and creative thinking abilities. Therefore, this model is recommended for use in other technology and vocational courses to promote innovation and deeper conceptual understanding.